Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1128/aac.00219-07
|View full text |Cite
|
Sign up to set email alerts
|

Increased Survival after Gemfibrozil Treatment of Severe Mouse Influenza

Abstract: Gemfibrozil, an agent that inhibits production of proinflammatory cytokines in addition to its clinically useful lipid-lowering activity, increased survival in BALB/c mice that were already ill from infection by influenza virus A/Japan/305/57 (H2N2). Gemfibrozil was administered intraperitoneally once daily from days 4 to 10 after intranasal exposure to the virus. Survival increased from 26% in vehicle-treated mice (n ‫؍‬ 50) to 52% in mice given gemfibrozil at 60 mg/kg/day (n ‫؍‬ 46) (P ‫؍‬ 0.0026). If this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 26 publications
(21 reference statements)
3
67
0
Order By: Relevance
“…Ethyl pyruvate was given either daily, from days 4 to 10 post infection (p.i.) as we have done previously for the drug gemfibrozil (20), or prophylactically, from 1 h before infection, and then daily, until day 10 p.i. …”
Section: Treatment With Ethyl Pyruvatementioning
confidence: 73%
“…Ethyl pyruvate was given either daily, from days 4 to 10 post infection (p.i.) as we have done previously for the drug gemfibrozil (20), or prophylactically, from 1 h before infection, and then daily, until day 10 p.i. …”
Section: Treatment With Ethyl Pyruvatementioning
confidence: 73%
“…Viral stock and infection procedures were as described previously (39). Briefly, stocks of influenza virus A/Japan/305/57 (A/Jap, H2N2), a negative ssRNA virus, were grown in embryonated eggs.…”
Section: Influenza Virus Infection Of Balb/c Mice and Localization Ofmentioning
confidence: 99%
“…83 A limited number of laboratory studies have shown the effectiveness of other immunomodulatory agents in mouse models of influenza. Post-infection treatment with resveratrol (a plant polyphenol with immunomodulatory activities) 84 and gemfibrozil 85 significantly improved survival in influenza virus-infected mice, and similar improvements have been demonstrated for pre-infection treatment with pioglitazone 86 and pioglitazone combined with AICAR, a metformin-like drug. 87 In two studies that evaluated the effects of treatment on virus replication, pulmonary virus levels were either unchanged 86 or reduced.…”
Section: The Host Response To Influenzamentioning
confidence: 60%
“…Influenza virologists usually use either inbred BALB/c or C57Bl/6 mice, 115 and these two strains have been used in all experimental studies of immunomodulatory agents. [84][85][86][87][88][89] These strains might not be optimal for determining which agent might best counteract the more intense inflammatory response in man. For example, in a study of host factors involved in the pathogenesis of pH1N1 virus influenza, BALB/c mice, which have a Th-2 bias, were shown to be less suitable than C57Bl/6 mice, which have a Th-1 bias.…”
Section: Acknowledgmentsmentioning
confidence: 99%